Comparative Study of Gas Alarm Detection System - Muhammad Ahmad Baballe; Mukhtar Ibrahim Bello; Abdulhamid Shariff Mahmoud (Journal of Telecommunication Control and Intelligent System, 2021)
Fires often occur due to negligence in using a gas stove. This paper was created in response to the increasing number of fires and explosions in today's world due to gas leaks. Key objectives about gas detection systems, their challenges, and the impact of using homes and organizations for security purposes. The gas detection system is a solution to reduce fire hazards. The installation of a gas alarm detection system is expected to help protect people's homes, organizations, hospitals, industries and institutions, especially with recent technological developments. Gas detection systems help control and monitor our homes for gas leaks that result in outbreaks and explosions.